(untitled) (Journal of Nepal Geological Society, 2013)
Groundwater samples collected at different locations in and around Delhi City were analysed for their physicochemical characteristics. Sampling locations were selected covering all the zones and samples were collected. The present investigation is focused on the determination of physicochemical parameters such as pH, total dissolved solids, total hardness, calcium hardness, turbidity, chlorides, sulphate, nitrate and fluoride. To assess the quality of groundwater, each parameter was compared with the standard desirable limit of that parameter in drinking water as prescribed by different agencies. The parameters were determined according to procedures outlined in the Standard Methods for the Examination of Water APHA. A systematic calculation was made to determine the correlation coefficient ’r’ amongst the parameters and the significant values of the observed correlation coefficient between the parameters was worked out. Suggestions were made to improve the quality of groundwater of Delhi area. The study of physico-chemic al characteristics of these groundwater samples suggest that the evaluation of water quality parameters as well as water quality management practices should be carried out periodically to protect the water resources.